论信息系统效用及其影响因素 - 谢新洲; 申宁 (情报理论与实践, 2003)
This paper views information systems in the perspective of users and suggests that the utility of information systems should be used as an important index to evaluate information systems.Based on a description of TTF theory and TAM model,this paper integrates and extends these two models to analyze the antecedent factors that have effects on the utility of information systems.
Keywords: information system; system model/TTF; TAM